2019
DOI: 10.4103/jpbs.jpbs_300_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of depth of penetration of root canal irrigant after using manual, passive ultrasonic, and diode laser–assisted irrigant activation technique

Abstract: AIM: The aim of this study was to compare and evaluate the penetration depth of irrigant after using manual, passive ultrasonic, and diode laser–assisted irrigant activation technique. Materials and Methods: Ninety extracted single-rooted human mandibular premolars were selected ( N = 90). Teeth were decoronated and working length was standardized for 12 mm. Root canals were shaped using ProTaper Universal F3. Saline was used as an irrigant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 27 publications
2
9
0
2
Order By: Relevance
“…Significant difference was seen between apical third and both middle and coronal thirds. This was consistent with Rajakumaran et al 33 and Ghorbanzadeh et al 16 study that showed highest penetration depth with laser activated irrigant in coronal third followed by middle and apical thirds. Highest penetration depth in coronal third could be attributed to thelarge and densely packed dentinal tubules seen in the coronal thirdof the root canal followed by middle third, while narrower tubules are located more in the apical thirds, and as a result can limit the ability of irrigant penetration.…”
supporting
confidence: 91%
“…Significant difference was seen between apical third and both middle and coronal thirds. This was consistent with Rajakumaran et al 33 and Ghorbanzadeh et al 16 study that showed highest penetration depth with laser activated irrigant in coronal third followed by middle and apical thirds. Highest penetration depth in coronal third could be attributed to thelarge and densely packed dentinal tubules seen in the coronal thirdof the root canal followed by middle third, while narrower tubules are located more in the apical thirds, and as a result can limit the ability of irrigant penetration.…”
supporting
confidence: 91%
“…Higher penetration seen in coronal third and middle third levels in the present study could be because of the larger tubular size of the dentin in the coronal part of the canal and the absence of complex anatomical structures. (42) Dentinal tubules hoard the maximum bacteria and thus must be cleaned effectively and efficiently. (43) In the present study, all the four root canal irrigants, NaOCl, CHX, Vitex negundo Linn.…”
Section: E N D O D O N T I C I N F E C T I O N C O N S I S T S O F a mentioning
confidence: 99%
“…Diante este cenário, o uso da irrigação ultrassônica passiva (PUI) tem surgido para complementar a limpeza biomecânica dos sistemas de canais radiculares, atingindo toda sua extensão. A irrigação ultrassônica passiva otimiza a ação do agente químico pela sua capacidade de cavitação e movimentação resultando no deslocamento dos detritos que impossibilitariam a ação da solução irrigadora no interior dos túbulos dentinários (Abu Rajakumaran and Ganesh 2019).…”
Section: Introductionunclassified